Biochemical and Electroretinographic Characterization of the Minipig Eye in the Context of Drug Safety Investigations. (September 2019) - Negro Silva, Luis Fernando; Li, Christian; de Seadi Pereira, Paula Juliana Brizuela; Tan, Wendy; Dubuc-Mageau, Michelle; Sanfacon, Audrey; Forster, Roy; Tavcar, Robert; Makin, Andy; Authier, Simon
Minipigs are an emerging nonrodent alternative for ocular toxicology owing to anatomical similarities in the minipig eyes when compared to humans. Ocular structures and components from Göttingen minipigs were characterized and compared to species commonly used in toxicology. Ocular reference data from Göttingen minipig including intraocular pressure, vitreous electrolyte and thiol concentration, and electroretinography (ERG) data are essential to model characterization and data interpretation during drug safety assessments. Intravitreal positive control agents including gentamicin, indocyanine green, and glycine were used to demonstrate ERG alterations caused by retinal cell toxicity, light transmission obstruction, or neurotransmission interferences, respectively. Electrolyte concentrations of the aqueous and vitreous humors from Göttingen minipigs were similar to other species including humans. The reference data presented herein supports the use of the Göttingen minipig as an alternate nonrodent species in ocular toxicology.